Probability and statistics for engineering and the sciences - Devore, Jay L. (Brooks/Cole - Cengage Learning, 2012)
This market-leading text provides a comprehensive introduction to probability and statistics for engineering students in all specialties. Devore emphasizes concepts, models, methodology, and applications as opposed to rigorous mathematical development and derivations. Aided by his lively and realistic examples, students go beyond simply learning about statistics - they also learn how to put statistical methods to use.